Penatalaksanaan Fisioterapi Pada Pasca Sectio Caesarea Di RSUD Dr. Moewardi Surakarta - Perwitasari, Nia, Wahyuni.S.Fis.,SKM.,M.Kes (2016)
Background: Patients with postoperative section caesarea will feel pain. Pain is a stressor that can cause stress and tension in which people can respond to biological and behavioral responses that cause physical and psychological. Gymnastics parturition puerperal able to avoid wetting due to stress, preventing the fall of the organs of the hip, treat sexual problems. Purpose: To know the benefits in the form of gymnastic exercise therapy in reducing postpartum pain, lower abdominal muscle spasm and improve functional ability. Results: Treatment of physiotherapy in the case of Post SectioCaesarea using gymnastics parturition for 2 times to get results with a decrease pain, decrease muscle spasm stomach and increased functional capabilities, it can be seen by the increase in abdominal muscle strength and improved functional capabilities that can be done by the patient, so that the post-partumexercise can reduce pain and decreased the abdominal muscle spasm and improve functional ability in patients Post Sectio Caesarea. Conclusions: Management of physiotherapy in the case of Post Sectio Caesarea usingexercise help reduce postpartum pain, lower abdominal muscle spasm and improve functional ability.